Effects of life history and reproduction on recruitment time lags in reintroductions of rare plants. Issue 3 (4th January 2019) - Albrecht, Matthew A.; Osazuwa‐Peters, Oyomoare L.; Maschinski, Joyce; Bell, Timothy J.; Bowles, Marlin L.; Brumback, William E.; Duquesnel, Janice; Kunz, Michael; Lange, Jimmy; McCue, Kimberlie A.; McEachern, A. Kathryn; Murray, Sheila; et al.
Abstract: Reintroductions are important components of conservation and recovery programs for rare plant species, but their long‐term success rates are poorly understood. Previous reviews of plant reintroductions focused on short‐term (e.g., ≤3 years) survival and flowering of founder individuals rather than on benchmarks of intergenerational persistence, such as seedling recruitment. However, short‐term metrics may obscure outcomes because the unique demographic properties of reintroductions, including small size and unstable stage structure, could create lags in population growth. We used time‐to‐event analysis on a database of unusually well‐monitored and long‐term (4–28 years) reintroductions of 27 rare plant species to test whether life‐history traits and population characteristics of reintroductions create time‐lagged responses in seedling recruitment (i.e., recruitment time lags [RTLs]), an important benchmark of success and indicator of persistence in reintroduced populations. Recruitment time lags were highly variable among reintroductions, ranging from <1 to 17 years after installation. Recruitment patterns matched predictions from life‐history theory with short‐lived species (fast species) exhibiting consistently shorter and less variable RTLs than long‐lived species (slow species). Long RTLs occurred in long‐lived herbs, especially in grasslands, whereas short RTLs occurred in short‐lived subtropical woody plants and annual herbs. Across plant life histories, as reproductive adult abundance increased, RTLs decreased. Highly variable RTLs were observed in species with multiple reintroduction events, suggesting local processes are just as important as life‐history strategy in determining reintroduction outcomes. Time lags in restoration outcomes highlight the need to scale success benchmarks in reintroduction monitoring programs with plant life‐history strategies and the unique demographic properties of restored populations. Drawing conclusions on the long‐term success of plant reintroduction programs is premature given that demographic processes in species with slow life‐histories take decades to unfold. Abstract : Article impact statement : Recruitment time lags vary across plant life histories and should be accounted for when evaluating success in rare‐plant reintroductions. Abstract : Efectos de la Historia de Vida y la Reproducción sobre las Demoras en el Tiempo de Reclutamiento en la Reintroducción de Plantas Raras Resumen: Las reintroducciones son componentes importantes de los programas de conservación y recuperación de especies raras de plantas, pero las tasas de éxito a largo plazo cuentan con muy poco entendimiento. Las revisiones previas de las reintroducciones de plantas se han enfocado en la supervivencia a corto plazo (p. ej.: ≤ 3 años) y en el florecimiento de individuos fundadores en lugar de enfocarse en puntos de referencia para la persistencia inter‐generacional, como el reclutamiento de plántulas. Sin embargo, las medidas a corto plazo pueden ocultar los resultados ya que las propiedades demográficas únicas de las reintroducciones, incluyendo el menor tamaño y la estructura inestable de estadio, podrían crear demoras en el crecimiento poblacional. Usamos un análisis de tiempo‐para‐evento en una base de datos de reintroducciones inusualmente bien monitoreadas y de largo plazo (4–28 años) de 27 especies raras de plantas para probar si los atributos de la historia de vida y las características poblacionales de la reintroducción crean respuestas con demoras temporales en el reclutamiento de plántulas (es decir, demoras temporales en el reclutamiento), un punto de referencia importante para el éxito y un indicador de la persistencia en poblaciones reintroducidas. Las demoras temporales de reclutamiento (RTLs, en inglés) fueron muy variables entre las reintroducciones, abarcando desde <1 hasta 17 años después de la instalación. Los patrones de reclutamiento se acoplaron a las predicciones de la teoría de historias de vida, donde las especies de vida corta (especies rápidas) exhibieron RTLs consistentemente más cortas y menos variables que las especies de vida larga (especies lentas). Las RTLs largas ocurrieron en hierbas de vida larga, especialmente en los pastizales, mientras que las RTLs cortas ocurrieron en plantas leñosas subtropicales de vida corta y en hierbas anuales. En todas las historias de vida de las plantas, conforme incrementó la abundancia de adultos reproductivos, las RTLs disminuyeron. Se observaron RTLs altamente variables en las especies con eventos de reintroducción múltiples, lo que sugiere que los procesos locales son igual de importantes que la estrategia de historia de vida para determinar los resultados de las reintroducciones. Las demoras temporales en los resultados de restauración resaltan la necesidad de poner a escala los puntos de referencia de éxito en los programas de monitoreo de reintroducciones que tengan estrategias de historia de vida de las plantas y las propiedades demográficas únicas de las poblaciones restauradas. La obtención de conclusiones sobre el éxito a largo plazo de los programas de reintroducción de plantas es algo prematuro ya que los procesos demográficos de especies con historias de vida lentas tardan décadas en desarrollarse. 摘要: 重引入是稀有植物保护和恢复计划的一个重要组成部分, 但其长期的成功率仍不得而知。对植物重引入已有的综述主要关注引入个体短期 (如三年内) 的存活和开花情况, 而不是以其跨代续存 (如幼苗更新) 为基准。然而, 短期指标可能会掩盖真实结果, 因为重引入物种有独特的种群统计特征, 包括小种群和不稳定的阶段结构, 可能导致种群增长存在滞后。我们用时间‐事件分析法, 对开展了非常好的监测的 27 种长期 (4 – 28年) 重引入植物的监测数据进行分析, 检验了重引入物种的生活史特性和种群特征是否会导致幼苗更新存在时间滞后响应 (即更新时滞), 这是重引入成功与否的重要基准, 也是重引入种群续存的一项指标。不同的重引入物种更新时滞 (recruitment time lags, RTL) 差异很大, 变化范围从栽种后不到一年到长达十七年。更新模式与生活史理论预测结果相吻合, 即相比于寿命长 (生长慢) 的物种, 寿命短 (生长快) 的物种RTL都更短、变异也更小。寿命长的草本植物RTL长, 特别是草原上的物种, 而寿命短的亚热带木本植物及一年生草本植物RTL则较短。在植物整个生活史中, RTL随着可繁殖成体的数量增加而下降。有多次重引入事件的物种RTL变异较大, 这表明局部过程与生活史策略在决定重引入结果上同等重要。恢复结果时滞效应的存在强调了利用恢复种群的植物生活史策略及特殊的种群统计特征来衡量重引入监测项目成功与否的必要性。鉴于生活史慢的物种可能需要几十年的时间来完成种群统计过程, 对植物重引入项目的长期成功下定论尚为时过早。【翻译: 胡怡思; 审校: 聂永刚】